Psychometric Properties of Eating Disordersand Body Image Questionnaire for Men (KBZOM II) - Pawłowska, Beata; Stankiewicz, Zofia; Potembska, Emilia (Current Problems of Psychiatry, 2012)
The article presents results of work on construction and determination of psychometric properties of Eating Disorders and Body Image Questionnaire for Men (KBZOM II), which is the second, extended version of Eating Disorder Questionnaire for Men (KBZOM), created by Pawłowska and Stankiewicz. KBZOM II questionnaire consists of 50 items and explained 63% of the variance. The questionnaire is formed by the following scales: Concentration on muscle mass, Overeating and coping with emotions, Negative body image associated with the sense of having excess body weight, Exercise addiction, Negative body image associated with the feeling of being not muscu-lar enough, Purging, Social acceptance. Cronbach’s alpha reliability coefficients for the various scales of KBZOM II are high and reach values of 0,93 to 0,72. The Questionnaire (KBZOM II) is short tool with good psychometric properties, used to study various dimensions of disordered attitudes towards eating and body image in men.